On the convergence of the nuclear field theory perturbation expansion for strongly anharmonic systems - Bortignon; P. F.; Broglia, A.; Bes, D. R. (Elsevier B.V., 1978)
Fil: Bortignon; P. F. The Niels Bohr Institute, University of Copenhagen; Dinamarca